Angiomyofibroblastoma: a very rare tumour of vulva - Verma, Urvashi; Nigam, Asha; ., Chandrakanta; Chowang, Romila; Bharti, Sadhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Angiomyofibroblastoma is a rare benign mesenchymal tumor of vulva. Patient had history of gradually increased mass over 6 years of duration. It was painless, fibro-cystic mass of 6.8×4.6×2.5 cm hanging over right side labia majora without any menstrual or coitus difficulty. Cosmetic and risk of malignancy were the main issues. After complete examination and investigations simple excision done. Histological examination revealed mass composed of numerous capillaries and some ectatic blood vessels embedded within the hyalinised matrix. No lipomatous component was found within the tumour. Nuclear atypism and pleomorphism were absent and mitotic figures were not detected. All these were suggestive of benign mesenchymal tumor, angiomyofibroblastoma.